Low-elongation and high-strength aramid sandwich PVC (Polyvinyl Chloride) material and preparation method thereof

By using tackifying resin to improve the paste layer in PVC mesh material, the problem of insufficient peel strength between aramid and PVC film is solved, and the number of folding resistance and service life of the material is significantly improved.

CN119567665AActive Publication Date: 2025-03-07SIJIA NEW MATERIAL (SHANGHAI) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411500600.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Among the existing PVC mesh materials, the peel strength between aramid and PVC film is insufficient, resulting in a short service life of the material under weight-bearing elongation.

Method used

By providing a paste layer on the surface of the aramid mesh layer and adding a tackifying resin to the paste layer, the bonding strength between the paste layer and the mesh layer is enhanced. The method of preparing tackifying resin includes adding a photoinitiator to acetone, dispersing and adding trifunctional aliphatic polyurethane acrylate and monomer, stirring and mixing to obtain mixed liquid A; adding resorcinol and a catalyst to water, dispersing and adding formaldehyde solution, and reacting to obtain mixed liquid B; blending mixed liquid A and mixed liquid B to obtain tackifying resin.

Benefits of technology

The peel strength between aramid and PVC film is improved, the number of folding resistance of the material is extended, and the service life of the material is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119567665A_ABST
    Figure CN119567665A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of PVC (polyvinyl chloride) sandwich net materials, and particularly discloses a low-extension and high-strength aramid sandwich net PVC material and a preparation method thereof. A low-extension and high-strength aramid sandwich net PVC material comprises an aramid net cloth layer, paste layers are arranged on the surfaces of the two sides of the aramid net cloth layer, and PVC adhesive film layers are arranged on the surfaces, away from the aramid net cloth layer, of the paste layers. The paste layer is prepared from the following raw materials: polyvinyl chloride resin, tackifying resin, a cross-linking agent, filler and a plasticizer; the preparation method of the tackifying resin comprises the following steps: adding a photoinitiator into acetone, dispersing, adding trifunctional aliphatic polyurethane acrylate and a monomer, and stirring and mixing to obtain a mixed solution A; adding resorcinol and a catalyst into water, dispersing, adding a formaldehyde solution, dispersing and reacting to obtain a mixed solution B; and blending the mixed solution A and the mixed solution B to obtain a finished product. The low-elongation and high-strength aramid sandwich PVC material disclosed by the invention is low in elongation rate, high in strength and high in peel strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of PVC mesh materials, and more specifically, to a low-elongation, high-strength aramid mesh PVC material and a preparation method thereof. Background Art

[0002] PVC mesh material is made of wire mesh sandwiched between two layers of PVC film. It has good softness, corrosion resistance, wear resistance, bending resistance, etc. It also has the advantages of waterproof, moisture-proof, and UV protection. It is widely used in membrane structure buildings, tents, rolling doors, truck canopies and protective covers and other fields.

[0003] Membrane structures and tent materials have requirements for the elongation of materials under load. For example, the elastic modulus must be used to design the cutting and lap length during design and processing. After construction, the surface will also be affected by the load, such as snow and water accumulation. As for rolling door materials, especially large rolling doors, the span reaches tens of meters or even hundreds of meters. There is a load-bearing rod underneath. Over time, the entire door curtain will grow more than one meter, which directly affects the use and appearance.

[0004] At present, there is a PVC sandwich material, the mesh of which is a polyester fiber mesh layer (polyester), and the characteristics of the polyester fiber mesh layer itself determine that it has high elongation and low strength, which is difficult to meet the requirements of membrane structures and tent materials in snow-laden and water-logged environments. In order to improve the above problems, some manufacturers will use aramid with low elongation and high strength instead of polyester, but the surface inertia of aramid leads to insufficient peeling strength between it and the PVC membrane, which affects the service life. Summary of the invention

[0005] In order to improve the peel strength between aramid and PVC film, the present application provides a low-elongation, high-strength aramid PVC sandwich material and a preparation method thereof.

[0006] In the first aspect, the present application provides a low-elongation, high-strength aramid mesh PVC material, which adopts the following technical solution: A low-elongation, high-strength aramid mesh PVC material, comprising an aramid mesh layer, both sides of the aramid mesh layer are provided with a paste layer, and the surface of the paste layer away from the aramid mesh layer is provided with a PVC film layer; The raw materials for preparing the paste layer include the following components in parts by weight: 90-100 parts of polyvinyl chloride resin, 3-5 parts of tackifying resin, 1-2 parts of cross-linking agent, 15-20 parts of filler, and 60-75 parts of plasticizer; the preparation method of the tackifying resin is: Add a photoinitiator to acetone, disperse it, then add trifunctional aliphatic polyurethane acrylate and monomer, stir and mix to obtain a mixed solution A; add resorcinol and a catalyst to water, disperse it, add formaldehyde solution, disperse it, react to obtain a mixed solution B; blend the mixed solution A and the mixed solution B to obtain.

[0007] By adopting the above technical solution: the aramid mesh layer is used as the base material, and its strength is 2.5-3 times that of polyester fiber, and its elongation at break is 3-5%, which is much lower than 25-40% of polyester fiber, giving the sandwich material the characteristics of low elongation and high strength. The paste layer is improved to solve the problem that the surface inertia of aramid leads to insufficient peeling strength between it and the PVC film layer: The tackifying resin is added, which is synthesized from resorcinol and formaldehyde. The hydroxymethyl in the main body undergoes a condensation reaction with the amide group in the aramid fiber molecule, and the oxygen atom of the phenolic hydroxyl group forms a hydrogen bond with the oxygen atom of the amide group, so that the paste layer is better attached to the surface of the aramid mesh layer, thereby improving the peel strength between the layers of the sandwich material. The trifunctional aliphatic polyurethane acrylate is further introduced, so that the tackifying resin first forms a highly flexible main body during the photocuring process, and then plasticizes and forms on this basis, reducing the problem of increased brittleness of the paste layer caused by the introduction of the tackifying resin.

[0008] After testing, the peel strength of the sandwich material without the addition of tackifying resin was 16.67 (25N / 5cm), and the folding times were only 235 times, which was easy to delaminate; after adding the tackifying resin, the peel strength of the sandwich material increased to more than 30.21 (25N / 5cm), and the folding times increased to more than 432 times, indicating that the tackifying resin effectively reduced the delamination problem; When a tackifying resin that does not contain mixed liquid A is added, the folding times of the sandwich material are only 337 times; when a tackifying resin of hexafunctional aliphatic polyurethane acrylate is added instead of a trifunctional aliphatic polyurethane acrylate, the folding times of the sandwich material are 398 times; when a tackifying resin that does not contain mixed liquid B is added, the peeling strength of the sandwich material is only 15.20 (25N / 5cm), indicating that tackifying resins that do not contain mixed liquid A or mixed liquid B, or are made with other functional acrylates cannot achieve better results.

[0009] Optionally, the weight ratio of the acetone, the photoinitiator, the trifunctional aliphatic polyurethane acrylate, and the monomer is 0.75:1.7-2.2:13-17:13-17.

[0010] By adopting the above technical solution: when the weight ratio of acetone, photoinitiator, trifunctional aliphatic polyurethane acrylate and monomer is within the above range, after the prepared tackifying resin is added to the paste layer, the performance of the prepared sandwich material is better.

[0011] Optionally, the monomer is a mixture of one or more of ethoxylated trimethylolpropane triacrylate, ethoxylated bisphenol A diacrylate, ethoxylated 1,6-hexanediol diacrylate, and ethoxylated pentaerythritol tetraacrylate.

[0012] By adopting the above technical solution: the above monomers can all be used to prepare the paste layer.

[0013] Optionally, the weight ratio of resorcinol to formaldehyde solution is 4:5.2-5.8.

[0014] By adopting the above technical solution: when the weight ratio of resorcinol to formaldehyde solution is within the above range, the performance of the prepared mesh material is better.

[0015] Optionally, the catalyst is an aqueous solution of sodium hydroxide.

[0016] Optionally, the weight ratio of the mixed liquid A to the mixed liquid B is 0.3-0.4:1.

[0017] By adopting the above technical solution: when the mixed liquid A and the mixed liquid B are within the above range, the ratio of the two is appropriate, and the prepared tackifying resin effectively enhances the bonding strength between the paste layer and the mesh layer, and the paste layer is not easy to be brittle.

[0018] Optionally, the cross-linking agent is dicumyl peroxide or di-tert-butyl peroxide isopropylbenzene.

[0019] By adopting the above technical solution: the present application appropriately increases the amount of the cross-linking agent to increase the peeling strength between the paste layer and the mesh layer.

[0020] In the second aspect, the present application provides a method for preparing a low-elongation, high-strength aramid sandwich PVC material, using the following technical solution: A method for preparing a low-elongation, high-strength aramid-web PVC material comprises the following steps: S1, mixing a plasticizer, a tackifying resin, a filler, and a cross-linking agent, adding a polyvinyl chloride resin, and mixing to obtain a paste; S2, coating the paste on the upper and lower surfaces of the aramid mesh layer, and sequentially subjecting the mixture to UV curing, drying and plasticization to form a paste layer to obtain a semi-finished product; S3, laminating the surface of the semi-finished product with the paste layer with the PVC film layer, cooling and shaping, and obtaining the product.

[0021] By adopting the above technical solution, the process is simple and the steps are few, which is conducive to the industrialized large-scale preparation of the sandwich material. The sandwich material is based on the low-elongation and high-strength aramid base cloth. In the process, it is first light-cured to form a high-flexibility main body, and then dried and plasticized, so that the sandwich material not only has a high peel strength, but also has a thick paste layer that is not easy to be brittle.

[0022] In summary, this application has the following beneficial effects: 1. The present application uses the aramid mesh layer as the base material to provide a low-elongation and high-strength main body, and further adds a homemade tackifying resin to the paste layer. The tackifying resin not only makes the paste layer better adhere to the surface of the aramid mesh layer, thereby improving the peeling strength between the layers of the sandwich material, but also makes it less brittle, so that the peeling strength of the sandwich material is increased to more than 30.21 (25N / 5cm), the folding endurance is increased to more than 432 times, the peeling strength is large, and the service life is long; 2. In this application, the amount of each component in the tackifying resin is controlled, and trifunctional aliphatic polyurethane acrylate is specifically used to provide a flexible main body to improve the brittleness problem after the tackifying resin is introduced; 3. The method of the present application has a simple process and fewer steps. It is first photocured to form a highly flexible main body, and then dried and plasticized, so that the sandwich material not only has a high peel strength, but also has a thick paste layer that is not easy to be brittle. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the overall structure of a low-elongation, high-strength aramid mesh PVC material in Example 1 of the present application.

[0024] Reference numerals: 1, PVC film layer; 2, paste layer; 3, aramid mesh layer. DETAILED DESCRIPTION

[0025] The present application is further described in detail below in conjunction with the examples. Except for the following special instructions, the raw materials are commercially available: trifunctional aliphatic polyurethane acrylate, purchased from Changxing Chemical Industry Co., Ltd., model ETERCURE6130B-80; Hexafunctional aliphatic polyurethane acrylate, purchased from Dongguan Jingshang New Materials Development Co., Ltd., model UV-6042; Ethoxylated bisphenol A diacrylate, purchased from Jining Tangyi Chemical Co., Ltd., model BPA3EODA; Chlorinated paraffin, purchased from Wuhan Xindongyi Chemical Co., Ltd., product number 14; Titanium dioxide, from Hebei Laiyi New Material Technology Co., Ltd., model BA-100; Polyvinyl chloride resin, purchased from Wuhan Jiyesheng Chemical Co., Ltd., model TYPE: SG5; Calcium zinc composite stabilizer, purchased from Shanghai Kaiyin Chemical Co., Ltd., model BPR618R; Zinc borate, purchased from Shandong Xinghai Chemical Co., Ltd., model XH-101; Antioxidant 1076, brand is BASF of Germany; Ultraviolet absorber UV-P, sourced from Jinan Lianghong Chemical Technology Co., Ltd.; Aramid mesh layer, sourced from Jiangsu Tiandi Zao New Material Technology Co., Ltd., weight 200g / m 2 , yarn count 32s, thickness 2mm; PVC film layer, sourced from Qingzhou Luxing Industry and Trade Co., Ltd., thickness 1mm.

[0026] Preparation Example 1 A tackifying resin is prepared by the following steps: 1.7 kg of photoinitiator 184 was added to 0.75 kg of acetone, and the mixture was stirred at 300 rpm for 10 min. Then, 13 kg of trifunctional aliphatic polyurethane acrylate and 13 kg of monomer (ethoxylated bisphenol A diacrylate) were added, and the mixture was stirred at 300 rpm for 20 min to obtain a mixed solution A. 0.4 kg of resorcinol and 0.13 kg of catalyst (10 wt% sodium hydroxide aqueous solution) were added to 7 kg of water, and the mixture was stirred at 500 rpm for 20 min. 0.52 kg of formaldehyde solution was added, and the mixture was reacted at 25° C. for 6 h to obtain a mixed solution B. Mix the mixed solution A and the mixed solution B at a weight ratio of 0.25:1 to obtain the product.

[0027] Preparation Example 2 A tackifying resin is prepared by the following steps: Add 2 kg of photoinitiator 184 to 0.75 kg of acetone, stir and mix at 300 rpm for 10 min, then add 15 kg of trifunctional aliphatic polyurethane acrylate and 15 kg of monomer (ethoxylated 1,6-hexanediol diacrylate), stir and mix at 300 rpm for 20 min to obtain a mixed solution A; 0.4 kg of resorcinol and 0.15 kg of a catalyst (a 10 wt% sodium hydroxide aqueous solution) were added to 7 kg of water, and the mixture was stirred at 500 rpm for 20 min. 0.55 kg of a formaldehyde solution was added, and the mixture was reacted at 25° C. for 6.5 h to obtain a mixed solution B. Mix the mixed solution A and the mixed solution B at a weight ratio of 0.25:1 to obtain the product.

[0028] Preparation Example 3 A tackifying resin is prepared by the following steps: 2.2 kg of photoinitiator 184 was added to 0.75 kg of acetone, and the mixture was stirred at 300 rpm for 10 min. Then, 17 kg of trifunctional aliphatic polyurethane acrylate and 17 kg of monomer (ethoxylated 1,6-hexanediol diacrylate and ethoxylated pentaerythritol tetraacrylate in a weight ratio of 1:1) were added, and the mixture was stirred at 300 rpm for 20 min to obtain a mixed solution A. 0.4 kg of resorcinol and 0.17 kg of catalyst (10 wt% sodium hydroxide aqueous solution) were added to 7 kg of water, and the mixture was stirred at 500 rpm for 20 min. 0.58 kg of formaldehyde solution was added, and the mixture was reacted at 25° C. for 7 h to obtain a mixed solution B. Mix the mixed solution A and the mixed solution B at a weight ratio of 0.25:1 to obtain the product.

[0029] Preparation Example 4-6 A tackifying resin, which is different from Preparation Example 2 in that the amount of mixed solution A is different, as follows: Preparation Example 4: The weight ratio of mixed solution A to mixed solution B is 0.3:1.

[0030] Preparation Example 5: The weight ratio of mixed solution A to mixed solution B is 0.35:1.

[0031] Preparation Example 6: The weight ratio of mixed solution A to mixed solution B is 0.4:1.

[0032] Comparative Preparation Example 1 A tackifying resin is prepared by the following steps: Add 0.4 kg of resorcinol, 0.15 kg of a catalyst (a sodium hydroxide solution with a concentration of 10 wt%) and a sodium hydroxide solution to 7 kg of water, stir and mix at 500 rpm for 20 min, add 0.55 kg of formaldehyde solution, and react at 25 ° C for 6 h to obtain the product.

[0033] Comparative Preparation Example 2 A tackifying resin is prepared by the following steps: Add 2 kg of photoinitiator 184 to 0.75 kg of acetone, stir and mix at 300 rpm for 10 min, then add 15 kg of trifunctional aliphatic polyurethane acrylate and 15 kg of monomer (ethoxylated 1,6-hexanediol diacrylate), stir and mix at 300 rpm for 20 min to obtain the product.

[0034] Comparative Preparation Example 3 A tackifying resin, which is different from Preparation Example 2 in that an equal amount of hexafunctional aliphatic urethane acrylate is used instead of trifunctional aliphatic urethane acrylate.

[0035] Examples 1-3, Comparative Examples 1-2 A low-elongation, high-strength aramid mesh PVC material, comprising an aramid mesh layer 3, both sides of the aramid mesh layer 3 are coated with a paste layer 2, and the surface of the paste layer 2 away from the aramid mesh layer 3 is adhered with a PVC film layer 1; The specific preparation method of the mesh PVC material is: S1, a plasticizer (chlorinated paraffin), a tackifying resin (prepared in Preparation Example 1), a filler (titanium dioxide) and a cross-linking agent were stirred and mixed at 100 rpm for 10 min, polyvinyl chloride resin, a calcium zinc composite stabilizer, a flame retardant (zinc borate), an antioxidant 1076, and an ultraviolet absorber UV-P were added, and the mixture was stirred and mixed at 120° C. for 15 min to obtain a paste; S2, apply the paste on the upper and lower surfaces of the aramid mesh layer 3 by a coating machine, with a coating amount of 7g / cm 3 Then, the films were cured by UV (using a high-pressure mercury lamp with a line power of 120 W / cm, a wavelength of 350 nm, and a radiation dose of 1000 mJ / cm 2 , time 20min), drying at 200℃ for 1.5min to plasticize, forming a paste layer 2, and obtaining a semi-finished product; S3. Use a laminating machine to laminat e the surface of the semi-finished product with the paste layer 2 with a PVC film at high temperature (laminating temperature 110°C, laminating speed 10m / min, laminating pressure 400N), and then cool and shape it with a cooling roller to obtain the product.

[0036] The ingredients and their corresponding weights in the raw materials for preparing the paste are shown in Table 1.

[0037] Table 1 Components and their weights in Examples 1-3 and Comparative Examples 1-2 (kg) Example 4-8, Comparative Example 4-6 A low-elongation, high-strength aramid sandwich PVC material, which is different from Example 2 in that the use of the tackifying resin is as shown in Table 2, but the amount of the tackifying resin in the paste remains unchanged.

[0038] Table 2 Usage of tackifying resin in Examples 4-8 and Comparative Examples 4-6 Example 4 5 6 7 8 Preparation Example of Tackifying Resin 2 3 4 5 6 Comparative Example 4 5 6 \ \ Comparative Preparation Example of Tackifying Resin 1 2 3 \ \ Performance Testing The following performance tests were performed on the mesh materials prepared in the examples and comparative examples, and the test results are recorded in Table 3.

[0039] Detection Methods 1. Peel strength test: Test according to DIN53357-82.

[0040] 2. Folding performance test: Cut each PVC mesh material to a size of 4.5cm*7cm, then use a blade to scratch a "cross" scratch on the surface of the PVC mesh material, and the scratch just cuts through the PVC film on its upper surface to obtain a sample. Then refer to the standard GB / T 4689.9-1984 to put the sample into the sample clamp for folding fastness test, where the upper clamp of the sample clamp is located in the "cross" scratch of the sample, and the lower clamp is fixed to the aramid mesh layer of the sample for testing, and the number of folding times is recorded.

[0041] Table 3 Performance test results project Peel strength (5N / 5cm) Folding resistance (times) Example 1 30.21 432 Example 2 31.45 458 Example 3 30.73 440 Example 4 31.70 467 Example 5 31.33 451 Example 6 30.89 495 Example 7 30.11 517 Example 8 29.64 530 Comparative Example 1 16.67 235 Comparative Example 2 22.39 318 Comparative Example 3 31.50 460 Comparative Example 4 32.11 337 Comparative Example 5 15.20 296 Comparative Example 6 30.14 398 Referring to Table 3, in Examples 1-3, due to the use of the tackifying resin prepared in Preparation Example 1, the peel strength of the prepared sandwich material reaches more than 30.21 (25N / 5cm) and the folding times reach more than 432 times. Compared with Example 2, Comparative Example 1 does not add tackifying resin, resulting in a significant decrease in the peel strength and folding times of the sandwich material. Compared with Example 2, Comparative Example 2 reduces the amount of tackifying resin, and the peel strength and folding times also decrease significantly. Combining Example 2 and Comparative Examples 1-2, it can be seen that the tackifying resin improves the bonding strength between the layers of the sandwich material and extends the service life.

[0042] The difference between Comparative Examples 4-6 and Example 2 is that: During the preparation of the tackifying resin, in Example 4, no mixed liquid A was added, resulting in a significant decrease in the number of folding times, which may be due to increased brittleness; in Example 5, no mixed liquid B was added, resulting in a significant decrease in peel strength, and no better tackifying effect was achieved; in Example 6, an equal amount of hexafunctional aliphatic polyurethane acrylate was used instead of trifunctional aliphatic polyurethane acrylate, and the number of folding times also decreased, which may also be due to the brittleness problem.

[0043] The difference between Example 4-5 and Example 2 is that the amounts of the components used in the preparation of the tackifying resin are different, and the performance of the prepared mesh material within the range of Examples 2 and 4-5 is better.

[0044] The difference between Examples 6-8 and Example 4 is that, during the preparation of the tackifying resin, the amount of mixed liquid A is increased, the peel strength of the prepared mesh material decreases slightly but still meets the use requirements overall, and the number of folding times increases significantly, and the performance of the prepared mesh material is more excellent.

[0045] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low-elongation, high-strength aramid mesh PVC material, comprising an aramid mesh layer (3), both sides of the aramid mesh layer (3) are provided with a paste layer (2), and the surface of the paste layer (2) away from the aramid mesh layer (3) is provided with a PVC film layer (1); characterized in that: The raw materials for preparing the paste layer (2) include the following components in parts by weight: 90-100 parts of polyvinyl chloride resin, 3-5 parts of tackifying resin, 1-2 parts of cross-linking agent, 15-20 parts of filler, 60-75 parts of plasticizer; The preparation method of the tackifying resin is: Add a photoinitiator to acetone, disperse it, then add trifunctional aliphatic polyurethane acrylate and monomer, stir and mix to obtain a mixed solution A; add resorcinol and a catalyst to water, disperse it, add formaldehyde solution, disperse it, react to obtain a mixed solution B; blend the mixed solution A and the mixed solution B to obtain.

2. The low-elongation, high-strength aramid-web PVC material according to claim 1, characterized in that: The weight ratio of the acetone, the photoinitiator, the trifunctional aliphatic polyurethane acrylate and the monomer is 0.75:1.7-2.2:13-17:13-17.

3. The low-elongation, high-strength aramid-net PVC material according to claim 2, characterized in that: The monomer is a mixture of one or more of ethoxylated trimethylolpropane triacrylate, ethoxylated bisphenol A diacrylate, ethoxylated 1,6-hexanediol diacrylate and ethoxylated pentaerythritol tetraacrylate.

4. The low-elongation, high-strength aramid-web PVC material according to claim 1, characterized in that: The weight ratio of resorcinol to formaldehyde solution is 4:5.2-5.

8.

5. The low-elongation, high-strength aramid-web PVC material according to claim 4, characterized in that: The catalyst is a sodium hydroxide aqueous solution.

6. The low-elongation, high-strength aramid-web PVC material according to claim 1, characterized in that: The weight ratio of the mixed solution A to the mixed solution B is 0.3-0.4:

1.

7. The low-elongation, high-strength aramid-web PVC material according to claim 1, characterized in that: The cross-linking agent is dicumyl peroxide or di-tert-butyl peroxycumene.

8. A method for preparing the low-elongation, high-strength aramid web PVC material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing a plasticizer, a tackifying resin, a filler, and a cross-linking agent, adding a polyvinyl chloride resin, and mixing to obtain a paste; S2, coating the paste on the upper and lower surfaces of the aramid mesh layer (3), and sequentially subjecting the mixture to UV curing, drying and plasticization to form a paste layer (2), thereby obtaining a semi-finished product; S3, laminating the surface of the semi-finished product with the paste layer (2) with the PVC film layer (1), cooling and shaping, and obtaining the product.

Citation Information

Patent Citations

  • Modified polyester fiber mesh cloth, PVC film structure material, and preparation method of modified polyester fiber mesh cloth and PVC film structure material

    CN103757911A

  • White light-curing water drop paint and preparation method and construction process thereof

    CN115785773A

  • Antistatic glue solution and application thereof

    CN118064079A

  • Environment-friendly PVC foaming material and preparation method thereof

    CN118531642A

  • Adhesive composition

    JP2003301157A